IMPLEMENTASI METODE TUTOR SEBAYA DAPAT MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA PELAJARAN KIMIA MATERI TERMOKMIA DIKELAS XI IPA 1 SMA NEGERI 1 INDRAPURI SEMESTER GANJIL TAHUN PELAJARAN 2018/2019 - Suryati Suryati (Lantanida Journal, 2018)
The aim of this study was to improve the learning outcomes and the student activity in the learning process of Chemistry in SMAN 1 Indrapuri of XI IPA 1 class. The solution to improve the student achievement was by the application of peer tutoring methods. This research was conducted in two cycles of 23 students. The technique of collecting data was conducted by the observation of teachers and collaborators. The KKM value of Chemistry lessons in this school is 65. Based on the results of the Cycle I was obtained around 65.21% passed the KKM with an average value of 61.3. The results of the cycle II showed the learning completeness as much as 100% with an average value of 72.4. This showed that the method of peer tutoring is successful in improving student learning outcomes. The student activity also increases with the presence of peer tutors. This showed that the use of peer tutors can improve student activity and student learning outcomes.